Exploring the virome of diseased horses - Li, Linlin; Giannitti, Federico; Low, Jason; Keyes, Casey; Ullmann, Leila Sabrina [UNESP]; Deng, Xutao; Aleman, Monica; Pesavento, Patricia A.; Pusterla, Nicola; Delwart, Eric (Microbiology Society, 2015)
Metagenomics was used to characterize viral genomes in clinical specimens of horses with various organ-specific diseases of unknown aetiology. A novel parvovirus as well as a previously described hepacivirus closely related to human hepatitis C virus and equid herpesvirus 2 were identified in the cerebrospinal fluid of horses with neurological signs. Four co-infecting picobirnaviruses, including an unusual genome with fused RNA segments, and a divergent anellovirus were found in the plasma of two febrile horses. A novel cyclovirus genome was characterized from the nasal secretion of another febrile animal. Lastly, a small circular DNA genome with a Rep gene, from a virus we called kirkovirus, was identified in the liver and spleen of a horse with fatal idiopathic hepatopathy. This study expands the number of viruses found in horses, and characterizes their genomes to assist future epidemiological studies of their transmission and potential association with various equine diseases.